2011
DOI: 10.1016/j.yjmcc.2010.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol depletion on compartmentalized cAMP responses in adult cardiac myocytes

Abstract: β1-Adrenergic receptors (β1ARs) and E-type prostaglandin receptors (EPRs) both produce compartmentalized cAMP responses in cardiac myocytes. The role of cholesterol-dependent lipid rafts in producing these compartmentalized responses was investigated in adult rat ventricular myocytes. β1ARs were found in lipid raft and non-lipid raft containing membrane fractions, while EPRs were only found in non-lipid raft fractions. Furthermore, β1AR activation enhanced the L-type Ca2+ current, intracellular Ca2+ transient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
97
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 47 publications
13
97
0
1
Order By: Relevance
“…This is consistent with enhanced sensitivity of functional responses to β1-AR stimulation, comparable with data obtained using MBCD to disrupt myocyte caveolae [16]. Increased adenylyl cyclase activity, by removal of the normal inhibitory influence of Cav3 [40], may contribute to this effect.…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with enhanced sensitivity of functional responses to β1-AR stimulation, comparable with data obtained using MBCD to disrupt myocyte caveolae [16]. Increased adenylyl cyclase activity, by removal of the normal inhibitory influence of Cav3 [40], may contribute to this effect.…”
Section: Discussionsupporting
confidence: 88%
“…Since we did not find a direct interaction between P2X 7 R and CAV1, we postulate that the enhanced P2X 7 R signaling in the absence of CAV1 could be due to difference in localization of P2X 7 R on the plasma membrane. Agarwal et al (1) observed similar changes in the functional response of a cell based on the localization of receptors in caveolae in adult cardiac myocytes. They found that the differences in the distribution of the ␤ 1 -adrenegic receptor (␤ 1 -AR) and the E-type prostaglandin receptors on the plasma membrane led to different functional responses, although activation of both of these receptors led to an increase in cAMP production.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, cholesterol depletion has been reported to reduce myocyte Ca 2ϩ currents and contraction under baseline conditions (6) and inhibit effects of ␤ 2 -AR activity (2,6). Nonetheless, other studies have identified amplified ␤ 1 -AR or ␤ 2 -AR signaling upon myocyte cholesterol depletion, with enhanced PKA/adenylyl cyclase phosphoregulation of target proteins (e.g., phospholamban and troponin I), and activation of Ca 2ϩ currents and myocyte contractile function (1,7,26). While we do not address ␤-AR responsiveness, our data for intact perfused hearts are consistent with inhibitory rather than stimulatory effects of cholesterol depletion on Ca 2ϩ -dependent myocyte function (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…In isolated cardiomyocytes, cholesterol depletion with methyl-␤-cyclodextrin (M␤CD) induces a negative inotropic effect at rest (6) while enhancing contractile responses to ␤ 2 -adrenergic receptors (ARs) (6,7,26) and ␤ 1 -ARs (1). In coronary smooth muscle, M␤CD impairs endothelin-1 and serotonin responses while enhancing phenylephrine contraction (40).…”
mentioning
confidence: 99%